'Australians are the Greatest Sport Loving People in the World': Sport Broadcasting's Role in the Development of National Radio in Australia, 1925–1935. Issue 4 (2nd October 2022) - Socolow, Michael J.
Abstract : Sport programming played a vital and catalytic role in the development of national relay and network broadcasting in the first decade of Australian radio. Sport programmes sold radio apparatuses, attracted listeners willing to pay for licenses, and provided live entertainment drawing large and appreciative audiences to radio relays throughout the nation. They also propagated a unifying ideal of Australian nationalism while helping develop a truly distinctive Australian model of radio production. By the end of the decade, the proficiency of Australian sport broadcasting would be recognized globally and used as a model by other broadcasting systems around the world.